Consulting role of internal auditors: The influencing factors and the impact on the firm’s growth opportunities and performance / Suhaily Shahimi - Suhaily , Shahimi (2016)
For the past few decades, the business environment has experienced rapid and revolutionary change with extensive consequences for organizations all over the world. In this radical changed phenomenon, internal auditing gained an important role in organizations. The Institute of Internal Auditors has delineated new changes on the definition of internal auditing which have widen the internal audit scope by explicitly incorporating consulting activities. Maximizing the internal audit function (IAF) is imperative to meet the challenges of today’s business environment and to add value to different stakeholders’ expectations. Yet, it has highlighted two issues i.e. internal auditors face the balancing act of dual roles (consulting and assurance) and stress of “to do more with less” in the current economic situations. Therefore, this study explores the consulting role of internal auditors in Malaysian context as it identifies factors that can influence its success and whether the internal audit contribution to consulting activities gives impact on firm’s growth opportunities and performance. Future growth is an important element to most companies especially to boost the economy of developing countries such as Malaysia. Stewardship theory is used to explain the internal audit role in consultancy and motivations created within IAF to support the board and audit committee in achieving organizational goals by providing professional advice. An exploratory study is conducted in Malaysian context as the study in internal audit consulting is relatively new. In preliminary stage, five interviews were conducted with the Chief Audit Executives of large Malaysian organizations to investigate the extent of consulting activities that internal auditors perform in Malaysia. Internal audit consulting’s survey instrument was developed based on past literature and exploratory interviews’ findings. A pilot study was conducted to gain feedback on the readability and clarity of the survey questions, to improve the scaling and the survey questions. For full data collection, these questionnaires were sent to all in-house internal audit departments (IADs) of public listed companies (417 companies) on Bursa Malaysia. Finally, in-depth interviews were conducted with 10 Chief Audit Executives in IAD from different organizations for further insights on issues of internal audit consulting and to validate the survey data. Random sample was adopted and the final number of sample was 112. The analyses included multivariate regression, reliability test, descriptive statistics, factor analysis and naming the factors. The results revealed that corporate governance variables i.e. 1) intentions/ambitions of IAD (all dimensions) and 2) expectations of board and audit committee (partially), influenced internal audit contribution to consulting activities. From survey and interview data, internal audit consulting was shown to influence firm’s growth opportunities and performance. It is inferred that IAF is effective in delivering their consulting job to help in achieving organizational goals. The quantitative and qualitative phases of empirical enquiry undertaken contributed significantly to the study. The interviews fully complimented survey questionnaires’ design as well as interpretation of results. Finally, this study highlights aspects of goal congruence and motivation derived within IAF as suggested by the stewardship theory to support the board audit committee to navigate the organization.